The politics of maternity - Mander, Rosemary; Murphy-Lawless, Jo. (Abingdon, Oxon : Routledge, 2013)
"A stimulating and thought-provoking analysis of the issues faced in the real world of midwifery and maternity care! Rosemary Mander discusses the context of contemporary childbearing and analyses a range of political in the broadest sense issues which need to be understood and addressed by those practising in a system of public maternity care, particularly the new midwife. Designed to help professionals cope with the transition from education and the ideals which brought them into health care to the reality of the system within which they learn and practise, this text includes successful strategies and lessons from which to learn. Drawing on recent and current international research, The Politics of Maternity demonstrates the commonality of the system-related challenges and develops some more constructive approaches to managing them, avoiding feelings of isolation and disengagement This inspiring book is designed to assist midwives to function and care effectively in a changing health care environment, rather than succumbing under pressure, for the benefit of mothers, babies and practitioners"--Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Pregnancy; Midwifery; Maternal health services; Electronic books